Perceptions of Flooding Risk and Water Resilience in the Southernmost City in California - Adriana Rios; Hassan Davani; Megan Welsh Carroll (Findings)
Imperial Beach (IB), situated at the southernmost point along the California coast, frequently experiences compound flooding, leading to the risk of stormwater pollution. This paper presents results from a brief survey (n=103) to examine IB residents’ views on persistent flooding challenges in IB, explore potential solutions to stormwater pollution, and identify barriers to adopting sustainable measures like rainwater harvesting practices (rain water harvesting). The findings indicate that participants are open to experimenting with rain water harvesting practices; however, a significant number lack familiarity with the proper utilization of these interventions, highlighting the need for easily accessible information and resources.